Impact of the recommendations of the British Pacing and Electrophysiology Group on pacemaker prescription and on the immediate costs of pacing in the Northern Region. Issue 11 (November 1992) - Ray, S G; Griffith, M J; Jamieson, S; Bexton, R S; Gold, R G
Abstract : Background —The report from the Working Party of the British Pacing and Electrophysiology Group recommends the use of more sophisticated pacemakers in most patients. These proposals were initially circulated in September 1990 and are likely to have major cost implications. Their impact on pacing practice and the immediate costs of pacemaker hardware in the Northern Region were retrospectively audited. Methods —The pacing records of 550 patients undergoing a first pacemaker insertion at the Freeman Hospital between March 1990 and August 1991 were reviewed. The patient's age, indication for pacing, pacing mode, and the cost of generator and lead(s) were recorded. The cost was compared with the costs of pacing with the optimal and alternative modes recommended by the Working Party. The costs were calculated from the actual mean cost of the recommended unit over the 18 month period of study multiplied by the number of patients who would have received that unit. Results —96% of patients were paced for sinus node dysfunction, atrioventricular block, or atrioventricular block and atrial fibrillation. The mean (SD) ages of patients in each diagnostic group were: sinus node dysfunction 69·4 (14), sinus node disease and atrioventricular block 67·2 (17·6), atrioventricular block 73·9 (12·5), atrial fibrillation and atrioventricular block 74·0 (13·9), and carotid sinus hypersensitivity 74·6 (11·6) years. Over the 18 month audit period there was an increase in physiological pacing. AAI pacing in patients with sinus node dysfunction increased by 100% and DDD pacing in atrioventricular block increased by 56%. Over the whole 18 month period the adoption of the British Pacing and Electrophysiology Groups optimal recommendations would have increased expenditure on pacemaker hardware in the Northern Region by 94% and the use of the alternative mode would have increased it by 61%. For the last six months alone the excess would be 78% and 48%. Conclusions The adoption of the recommendations of the British Pacing and Electrophysiology group in the Northern Region would greatly increase the cost of pacing hardware. The greater part of this increase would be attributable to the routine use of dual chamber pacing in patients with atrioventricular block and the increased use of rate responsive units. The benefits of sophisticated pacing in a predominantly elderly population need to outweigh the disadvantages of the increased cost and complexity of follow up.